Survey of influenza and other respiratory viruses diagnostic testing in US hospitals, 2012–2013. Issue 2 (29th January 2016) - Su, Su; Fry, Alicia M.; Kirley, Pam Daily; Aragon, Deborah; Yousey‐Hindes, Kimberly; Meek, James; Openo, Kyle; Oni, Oluwakemi; Sharangpani, Ruta; Morin, Craig; Hollick, Gary; Lung, Krista; et al.
Abstract : Background: Little is known about laboratory capacity to routinely diagnose influenza and other respiratory viruses at clinical laboratories and hospitals. Aims: We sought to assess diagnostic practices for influenza and other respiratory virus in a survey of hospitals and laboratories participating in the US Influenza Hospitalization Surveillance Network in 2012–2013. Materials and Methods: All hospitals and their associated laboratories participating in the Influenza Hospitalization Surveillance Network (FluSurv‐NET) were included in this evaluation. The network covers more than 80 counties in 15 states, CA, CO, CT, GA, MD, MN, NM, NY, OR, TN, IA, MI, OH, RI, and UT, with a catchment population of 28 million people. We administered a standardized questionnaire to key personnel, including infection control practitioners and laboratory departments, at each hospital through telephone interviews. Results: Of the 240 participating laboratories, 67% relied only on commercially available rapid influenza diagnostic tests to diagnose influenza. Few reported the availability of molecular diagnostic assays for detection of influenza (26%) and other viral pathogens (≤20%) in hospitals and commercial laboratories. Conclusion: Reliance on insensitive assays to detect influenza may detract from optimal clinical management of influenza infections in hospitals.